Impacts of dietary silver nanoparticles and probiotic administration on the microbiota of an in-vitro gut model. (February 2019) - Cattò, Cristina; Garuglieri, Elisa; Borruso, Luigimaria; Erba, Daniela; Casiraghi, Maria Cristina; Cappitelli, Francesca; Villa, Federica; Zecchin, Sarah; Zanchi, Raffaella
Abstract: Ingestion of silver nanoparticles (AgNPs) is inevitable linked to their widespread use in food, medicines and other consumer products. However, their effects on human microbiota at non-lethal concentrations remain poorly understood. In this study, the interactions among 1 μg mL −1 AgNPs, the intestinal microbiota, and the probiotic Bacillus subtilis (BS) were tested using in-vitro batch fermentation models inoculated with human fecal matter. Results from metagenomic investigations revealed that the core bacterial community was not affected by the exposure of AgNPs and BS at the later stage of fermentation, while the proportions of rare species changed drastically with the treatments. Furthermore, shifts in the Firmicutes/Bacteriodetes (F/B) ratios were observed after 24 h with an increase in the relative abundance of Firmicutes species and a decrease in Bacteroidetes in all fermentation cultures. The co-exposure to AgNPs and BS led to the lowest F/B ratio. Fluorescent in-situ hybridization analyses indicated that non-lethal concentration of AgNPs negatively affected the relative percentage of Faecalibacterium prausnitzii and Clostridium coccoides / Eubacterium rectales taxa in the fermentation cultures after 24 h. However, exposure to single and combined treatments of AgNPs and BS did not change the overall diversity of the fecal microflora. Functional differences in cell motility, translation, transport, and xenobiotics degradation occurred in AgNPs-treated fermentation cultures but not in AgNPs+BS-treated samples. Compared to the control samples, treated fecal cultures showed no significant statistical differences in terms of short-chain fatty acids profiles, cytotoxic and genotoxic effects on Caco-2 cell monolayers. Overall, AgNPs did not affect the composition and diversity of the core fecal microflora and its metabolic and toxic profiles. This work indicated a chemopreventive role of probiotic on fecal microflora against AgNPs, which were shown by the decrease of F/B ratio and the unaltered state of some key metabolic pathways. Graphical abstract: Highlights: Interactions among AgNPs, the intestinal microbiota, and a probiotic were tested. AgNPs did not affect the core fecal microflora and its metabolic and toxic profiles. Functional differences in few critical pathways occurred in AgNPs-treated samples. The probiotic had a chemopreventive role on fecal microflora against AgNPs. Abstract : This work will contribute to better understand the effects of non-lethal concentrations of AgNPs on the gut microbiota, and their interactions with probiotic administrations.